Association of visceral fat and plasmacytoid dendritic cell-derived interferon alpha with SARS-CoV-2 infection - Naoki Ozato; Shota Hori; Nobuyuki Miyai; Hideto Takase; Ryohei Tsuji; Noriko Osaki; Daisuke Fujiwara; Mikio Arita (PLoS ONE, 2026)
Type I interferon (IFN-I: IFNα/β) production by plasmacytoid dendritic cells (pDCs) is critical for controlling viral infections. Visceral fat obesity is associated with severe outcomes in viral infections, but its effect on pDC-mediated IFN-I production in the context of SARS-CoV-2 infection remains unclear. This cross-sectional study evaluated cytokine production by blood pDCs in response to TLR7/8 stimulation and analyzed its association with visceral fat area (VFA). IFN-I production was exclusively observed in pDCs following TLR7/8 stimulation. The proportion of IFNα-positive pDCs (pDC-IFNα) was significantly lower in individuals with high VFA (above the median) and negatively correlated with VFA (r = −0.27, P < 0.001). Logistic regression revealed that high VFA or low pDC-IFNα levels (below the median) were independently associated with a history of SARS-CoV-2 infection. Moreover, individuals with both high VFA and low pDC-IFNα levels had significantly higher odds of infection compared to those with low VFA and high pDC-IFNα levels. These findings suggest a potential relationship between VFA and impaired pDC function, which may influence susceptibility to SARS-CoV-2 infection. Managing VFA and enhancing pDC responses might represent strategies to reduce infection risk in individuals with visceral fat obesity.